Characterization methodology and impact analysis in the medium of higher education institutions’ graduates - Parra Castrillón, José Eucario; Arias Giraldo, Sandra Milena (Cooperativismo & Desarrollo, 2017)
Purpose: This article is a product of the research "Graduates’ of the Universidad de San Buenaventura in Medellín characterization and medium’s impact analysis ", developed between June 2014 and August 2015, by an interdisciplinary team of professionals in the areas of engineering, architecture, psychology, education, accounting, law and communication. Description: The objectives of the research were to characterize the graduates in personal, academic and labor aspects, as well as to analyze their impact in their fields of action and influence. Point of view: This article does not pretend to reveal the results of the investigation, since they constitute information of internal interest for the institution. It aims at presenting a methodological proposal that can serve as reference point for the graduates’ follow-up task performed by Higher Education Institutions. It therefore seeks to contribute in two preponderant issues: avoiding the reduction of such studies to the mere application of a survey, and encouraging an interdisciplinary scientific research methodology. Conclusions: The method is relevant because it comprises several phases and instruments. It comprised a mixed and multidimensional research that compiled information through qualitative, quantitative and documentary techniques, using various sources of information. Additionally, the way the real size of the population was interpreted represents a novelty for studies about graduates.